MANAJEMEN BERBASIS SEKOLAH DALAM PENINGKATAN KUALITAS PENDIDIKAN ISLAM - Kartika Susanti (UNISAN JURNAL, 2024)
Islamic education is an important aspect in shaping individual character and morality and strengthening the foundations of the Muslim faith. In this context, the implementation of a school-based management model has been recognized as an effective approach in improving the quality of Islamic education. This abstract presents the results of research on the implementation of a school-based management model in improving the quality of Islamic education. Through literature studies and data analysis from various sources, this research highlights the important role of school-based management models in providing flexibility and independence for schools in managing resources, designing curricula, and making decisions in accordance with Islamic educational values. Research findings also show that teacher competency, community participation, and the use of information and communication technology are key factors in the successful implementation of this model. Financial challenges and relevant curriculum development are also a focus in this abstract. In conclusion, the implementation of a school-based management model has great potential in improving the quality of Islamic education, but requires comprehensive support from various parties to achieve optimal results. With strong collaboration and strong commitment, Islamic education can continue to develop and make a significant contribution in shaping a better future for Muslims.